Pustakawan masa depan: Menjawab tantangan disrupsi profesi pustakawan - Mufid Mufid (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2021)
In the era of disruption, librarians face complex challenges to continue to play a role (value) and positively impact the information society. This paper aims to try to provide a view of the skills needed for the future librarian profession. The librarian profession can survive in an era of uncertainty depending on the skills of today's librarians to see future challenges and how to implement them in the present.